PENGARUH HARGA SAHAM, RETURN ON EQUITY, DAN KAPITALISASI BIAYA TERHADAP INCOME SMOOTHING - Diah Armeliza (Jurnal Ilmiah Wahana Akuntansi, 2019)
This study aims to examine the effect of stock prices, return on equity and cost capitalization on income smoothing in the plantation sub-sector listed on the Indonesia Stock Exchange. The research period is five years, namely 2014-2018. The study used secondary data in the form of financial statements from the Indonesia Stock Exchange (IDX). The sample was companies listed in the plantation sub-sector successively in the period 2014-2018. The research used a purposive sampling method with a sample of 32. Data analysis used multiple linear regression with a significance level of 5%. The results showed that cost capitalization affected the income smoothing practices which was proxied using the Eckel index, while stock prices and return on equity do not affect income smoothing practices.